2023
DOI: 10.3390/jfb14060297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dental Titanium Implants with Different Surface Treatments Using Femtosecond and Nanosecond Lasers on Biofilm Formation

Abstract: This study aimed to evaluate the impact of different surface treatments (machined; sandblasted, large grit, and acid-etched (SLA); hydrophilic; and hydrophobic) on dental titanium (Ti) implant surface morphology, roughness, and biofilm formation. Four groups of Ti disks were prepared using distinct surface treatments, including femtosecond and nanosecond lasers for hydrophilic and hydrophobic treatments. Surface morphology, wettability, and roughness were assessed. Biofilm formation was evaluated by counting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Another study investigated how different surface treatment methods, including femtosecond and nanosecond laser processing, affect the surface morphology, roughness, and biofilm formation of dental titanium implant discs, and found that in the early stages of biofilm growth, Aa levels were significantly higher in the hydrophilic treatment group than in the hydrophobic treatment group. Although lower in the treated group, after 72 h, the biofilm growth was similar in both groups [28].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another study investigated how different surface treatment methods, including femtosecond and nanosecond laser processing, affect the surface morphology, roughness, and biofilm formation of dental titanium implant discs, and found that in the early stages of biofilm growth, Aa levels were significantly higher in the hydrophilic treatment group than in the hydrophobic treatment group. Although lower in the treated group, after 72 h, the biofilm growth was similar in both groups [28].…”
Section: Discussionmentioning
confidence: 77%
“…Various studies have demonstrated that the use of femtosecond laser technology can form nano-textured grooves [16] and grids [17]. A previous study evaluated the formation of biofilms by treating the surface of titanium implants using femtosecond and nanosecond lasers and changing the surface modification to hydrophilic and hydrophobic properties [28].…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatment can change the wettability of titanium materials, but it depends on the chosen surface topography. Therefore, different authors report both hydrophobic and hydrophilic surfaces created by nanosecond and femtosecond lasers [57][58][59]. Bacteria can adhere to materials with low hydrophilicity through hydrophobic interactions.…”
Section: Bacterial Adhesionmentioning
confidence: 99%
“…Recent advances in laser technology have allowed the simultaneous generation of meso- and nano-topographies on metallic surfaces [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Particular studies utilizing solid-state laser etching created a unique meso-and-nano hybrid zirconia surface on which the meso-topography mimics “cactus-like” oscillating spikes, while the nano-topography consists of dense, nodular protrusions, 100–300 nm in diameter, resembling trabecular bone [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%